Modern Pedagogical Approaches to Developing Aesthetic and Creative Skills in Art Education - Raxmonova E’zoza Zoir qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This article explores modern pedagogical approaches to enhancing students’ aesthetic and creative skills in art education. It emphasizes the use of interactive lessons, project-based learning, digital tools, and student-centered strategies to develop visual thinking, artistic perception, and creative expression. The study also highlights the importance of providing a supportive and culturally enriched learning environment that fosters originality and critical engagement with art.